#### Answer

$-5x + y = 13$

#### Work Step by Step

The equation given is in point-slope form, which is given by the formula:
$y - y_1 = m(x - x_1)$
Therefore, we can see that $5$ is the slope for the given equation and is also the slope for the graph we are looking for.
Since we now have a point on the graph and the slope of the graph, we can now plug in these values into point-slope form:
$y - (-7) = 5(x - (-4))$
Let's simplify the operations:
$y + 7 = 5(x + 4)$
We need to rewrite this equation in standard form ($Ax + By = C$). First, we need to use the distributive property on the right side of the equation:
$y + 7 = 5x + 20$
$-5x + y + 7 = 20$
Now, we move constants to the right side of the equation by subtracting $7$ from both sides of the equation:
$-5x + y = 13$